Effect of Na doping on photoluminescence and laser stimulated nonlinear optical features of ZnO nanostructures. (October 2019) - Deekshitha, U.G.; Upadhya, Krithika; Antony, Albin; Ani, Aninamol; Nowak, M.; Kityk, I.V.; Jedryka, J.; Poornesh, P.; Manjunatha, K.B.; kulkarni, Suresh D.
Abstract: In this work, nonlinear optical properties of Na: ZnO thin films (Na: ZnO) have been experimentally elaborated. The principal possibility to operate the nonlinear optical features using external laser beams is shown. The Na: ZnO films were synthesized by spray pyrolysis technique at a deposition temperature equal to about 400 °C. XRD graph reveals that the grown films were polycrystalline in nature with a dominant peak corresponding to (0 0 2) plane. Despite the difference in the ionic radii of the Na (0.95A o ) and Zn (0.74A°), an angle shift in the XRD peak was not observed, whereas there was a significant change in peak intensity. The photoluminescence (PL) spectra resulted in three emission centres spectrally situated in violet, blue and green colour region due to the presence of native defect states in the forbidden energy gap. Second and third harmonic generation (SHG, THG) experiments stimulated by external coherent light beams show the existence of THG maxima for 15% Na doped Zn:O which was quite different with respect to SHG maximum for pure ZnO. The main innovation of this work is the possibility to change nonlinear optical susceptibility varying Na doping concentration and by coherent laser treatment, contrary to the previous works where these parameters have not been explored.